2016
DOI: 10.1016/j.bpj.2016.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin Diffusion in Supported Lipid Bilayers Exhibits Calcium-Dependent Dynamic Heterogeneity

Abstract: Ca 2þ ions are critical to cadherin ectodomain rigidity, which is required for the activation of adhesive functions. Therefore, changes in Ca 2þ concentration, both in vivo and in vitro, can affect cadherin conformation and function. We employed single-molecule tracking to measure the diffusion of cadherin ectodomains tethered to supported lipid bilayers at varying Ca 2þ concentrations. At a relatively high Ca 2þ concentration of 2 mM, cadherin molecules exhibited a fast diffusion coefficient that was identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…As is apparent from Figure 1B–J , transport properties are often coupled to the FRET-state of a molecule. This is because the FRET-state reflects the oligomeric state of an E-cad molecule, and large oligomers diffuse slower than a monomer due to increased protein-lipid interactions, which is the primary source of drag ( Cai et al, 2016 ). In order to assess this hypothesis and confirm that the high-FRET state does in fact correlate with protein clusters involving a donor and one or more acceptors, the average short-time diffusion coefficient ( ) was determined for the high and low FRET-state populations independently.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As is apparent from Figure 1B–J , transport properties are often coupled to the FRET-state of a molecule. This is because the FRET-state reflects the oligomeric state of an E-cad molecule, and large oligomers diffuse slower than a monomer due to increased protein-lipid interactions, which is the primary source of drag ( Cai et al, 2016 ). In order to assess this hypothesis and confirm that the high-FRET state does in fact correlate with protein clusters involving a donor and one or more acceptors, the average short-time diffusion coefficient ( ) was determined for the high and low FRET-state populations independently.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, due to inherent defects in supported lipid bilayers, a permanently immobile (or highly confined) population was observed in the donor channel ( Knight et al, 2010 ). Traditionally, a displacement-based trajectory filtering procedure or photobleaching is applied to remove these slowly diffusing trajectories in lipid bilayer studies ( Cai et al, 2016 ; Chaparro Sosa et al, 2018 ; Chung et al, 2016 ; Knight and Falke, 2009 ; Knight et al, 2010 ; Ziemba and Falke, 2013 ). However, we opted to instead use a median donor intensity trajectory exclusion criterion, as this removed many bright contaminants, donor aggregates, and donor E-cad labeled with multiple fluorophores, but did not accidentally remove slowly diffusing E-cad clusters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that the diffusion of LB‐tethered proteins is controlled by the hydrodynamic coupling between the tethered protein and the bilayer, which is a function of the strength of protein‐lipid interactions and the effective size of the protein‐bilayer interface. [ 39–42 ] Notably, we previously found that unfolded NfsB diffused more slowly than folded NfsB, [ 33 ] reflecting stronger interactions between the LB and the unfolded state of the enzyme, which led to increased friction due to greater contact between the unfolded state and the LB. As in our previous work, D̅ folded and D̅ unfolded were determined from complementary cumulative square displacement distributions for each state, which were fit to a Gaussian mixture model with two diffusive modes, and the mean diffusion coefficients were calculated as the weighted average of the two modes.…”
Section: Resultsmentioning
confidence: 99%
“…Lipids were dried under nitrogen gas, and subsequently rehydrated in buffer containing sodium phosphate (10 × 10 –3 m ) and sodium chloride (800 × 10 –3 m ) at a pH of 8.0 followed by extrusion to form unilamellar vesicles with diameter of 50 nm as described previously. [ 39 ]…”
Section: Methodsmentioning
confidence: 99%